2022
DOI: 10.1007/s10980-022-01416-w
|View full text |Cite
|
Sign up to set email alerts
|

Day versus night use of forest by red and roe deer as determined by Corine Land Cover and Copernicus Tree Cover Density: assessing use of geographic layers in movement ecology

Abstract: Context Diel use of forest and open habitats by large herbivores is linked to species-specific needs of multiple and heterogeneous resources. However, forest cover layers might deviate considerably for a given landscape, potentially affecting evaluations of animals’ habitat use. Objectives We assessed inconsistency in the estimates of diel forest use by red and roe deer at GPS location and home range (HR) levels, using two geographic layers: Tree Cover Den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…A notable deviation from this pattern was represented by the red squirrel, the smallest species of our sample, whose detections were concentrated during daylight, and which strongly responded to human disturbance by decreasing its site use. That diurnal site use decreased with greater extents of open habitat at meta-community level is in line with previous research highlighting a daily shift of space use by mammals between closed and open habitats in relation to exposure to human disturbance and hunting risk, with animals seeking cover under dense forest stands during the peak of human activity at daylight and selecting clearings and open areas during darkness [38,53]. This suggests that the effects of human presence on mammals could be influenced by habitat structure, with habitat suitability therefore changing between daylight, night and twilight hours (e.g.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A notable deviation from this pattern was represented by the red squirrel, the smallest species of our sample, whose detections were concentrated during daylight, and which strongly responded to human disturbance by decreasing its site use. That diurnal site use decreased with greater extents of open habitat at meta-community level is in line with previous research highlighting a daily shift of space use by mammals between closed and open habitats in relation to exposure to human disturbance and hunting risk, with animals seeking cover under dense forest stands during the peak of human activity at daylight and selecting clearings and open areas during darkness [38,53]. This suggests that the effects of human presence on mammals could be influenced by habitat structure, with habitat suitability therefore changing between daylight, night and twilight hours (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…The distances from each camera station to the closest settlement were computed as the Euclidean distance and represented proximity to town centres as reported by the Corine Land Cover 2018 pan-European raster map [37] (therefore excluding isolated houses). Previous research has shown that spatio-temporal habitat use by forest mammals is influenced by the amount of open habitat [38]; we therefore extracted the proportion of open habitat in a 1 km 2 buffer around each camera trapping site using the Tree Cover Density 2018 pan-European raster dataset [37], and a threshold of 10% tree cover to distinguish between open and forest habitat, following the Food and Agriculture Organization (FAO) official categorization of forest [39]. Site elevation and site slope were used to correct for possible further environmental influences while investigating focal anthropogenic effects on mammals, and were extracted from digital elevation models (DEMs) by using the built-in tools for geospatial analyses in QGIS [40].…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, similar to past work we detected a small signal of deer using developed landcovers more at night compared to daytime hours (Roden-Reynolds et al, 2022). If this pattern holds true beyond this study, this diel activity pattern supports global meta-analyses showing increased wildlife nocturnality in response to human activity (Gaynor et al, 2018, see Bonnot et al, 2020 for deer specific analysis) and provides evidence of anthropogenic-driven alteration of deer space use (Salvatori et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…For example, forest canopy can provide cover from adverse conditions (e.g., deep snow: Mysterud and Østbye 1995, Ewald et al 2014, Ossi et al 2015 and protection from predators or human disturbance (Bonnot et al 2013), while the understorey provides seasonally rich foraging (i.e., during the vegetation green up and re-growth, Mancinelli et al 2015). In contrast, open areas may be used by ungulates as a seasonal source of forage (Abbas et al 2011), but mainly at night to avoid human disturbance (Godvik et al 2009;Bonnot et al 2013;Dupke et al 2017;Salvatori et al 2022), or to diminish the risk of ambush predation (Lone et al 2014;Gehr et al 2017). Hiding cover may also be seasonally available in open habitats, for example, in summer, when row crops are mature and provide concealing (Mysterud et al 1997;Bjørneraas et al 2011;Bonnot et al 2013;Dupke et al 2017).…”
Section: Introductionmentioning
confidence: 99%